Effect of Mn-substitution on the structure Co0.6Zn0.4Fe2O4. Issue 1 (March 2021) - Hasan, N.; Hadi, Mohammed H.
Abstract: One Ferrite is a ferromagnetic substance where it is ideally used to manufacture devices such as rectifiers, memory devices, and inductors hearts as well as for various applications of microwave waves. The electrical and structural characterization of ferrites depends on preparation methods, nature of dopant, and dopant concentration. For these reasons, the series samples of Co0.6Zn0.4MnxFe2−xO4 ferrites prepared, using a traditional ceramic process, Mn-Zn ferrites were synthesized and sintered up to 1200 °C for 5 hours. We tested the X Ray diffraction (XRD) for different Mn-substitution (where x = 0, 0.2, and 0.4). XRD studies confirmed that the sample's structural have a cubic spinel phase. The electrical characterization (such as conductivity, real and imaginary dielectric constant) was measured and discussed, as well.